G Protein-Coupled Estrogen Receptor 1 Regulates Human Neutrophil Functions - Rodenas, M. Carmen (Biomed Hub, 2017)
BACKGROUND: The role of estrogens in immune functioning is relatively well known under both physiological and pathological conditions. Neutrophils are the most abundant circulating leukocytes in humans, and their abundance and function are regulated by estrogens, since they express estrogen receptors (ERs). Traditionally, estrogens were thought to act via classical nuclear ERs, namely ERα and ERβ. However, it was observed that some estrogens induced biological effects only minutes after their application. This rapid, “nongenomic” effect of estrogens is mediated by a membrane-anchored receptor called G protein-coupled estrogen receptor 1 (GPER1). Nevertheless, the expression and role of GPER1 in the immune system has not been exhaustively studied, and its relevance in neutrophil functions remains unknown. METHODS: Human neutrophils were incubated in vitro with 10-100 µ<smlcap>M</smlcap> of the GPER1-specific agonist G1 alone or in combination with lipopolysaccharide. GPER1 expression and subcellular localization, respiratory burst, life span, gene expression profile, and cell signaling pathways involved were then analyzed in stimulated neutrophils. RESULTS: Human neutrophils express a functional GPER1 which regulates their functions through cAMP/protein kinase A/cAMP response element-binding protein, p38 mitogen-activated protein kinase, and extracellular regulated MAPK signaling pathways. Thus, GPER1 activation in vitro increases the respiratory burst of neutrophils, extends their life span, and drastically alters their gene expression proﬁle. CONCLUSIONS: Our results demonstrate that GPER1 activation promotes the polarization of human neutrophils towards a proinflammatory phenotype and point to GPER1 as a potential therapeutic target in immune diseases where neutrophils play a key role.